Cover Berkala Arkeologi Volume 13 Edisi Khusus 1993 - Berkala Arkeologi (Berkala Arkeologi, 1993)
Special Edition consisting of 8 articles discussing the Wonoboyo Site. This newly found site was discovered during 1990s in Central Java, consisting of various gold artifacts.